ECTOPIC PREGNANCY IN A MALABARI DOE - NAVEEN KUMAR, R H; JAYAKUMAR, C; SHRAVYA, G S; SUDHA, C M (The Indian Journal of Animal Reproduction, 2017)
A Malabari doe with overdue pregnancy was presented with no typical evidence of kidding. On abdominalpalpation, a firm mass was palpated which was tentatively diagnosed as ectopic pregnancy, and was furtherconfirmed by trans-abdominal sonography. The ectopic fetus was removed by laparotomy. The presence ofmesenteric vegetative attachments of placenta and completely involuted uterus without any uterine scar signifiedthe occurrence of ectopic pregnancy at an early stage.
Keywords: Doe; Ectopic; Extrauterine; Laparotomy; Pregnancy